Subject-specific computational modeling of acromioclavicular and coracoclavicular ligaments - Flores, Cesar; Celik, Haluk; Hoenecke, Heinz; D’Lima, Darryl D. (Journal of shoulder and elbow surgery, 2023)
Disruption of the acromioclavicular joint is a common injury. Despite the different surgical procedures described for treating this injury, complications such as loss of reduction and failure of fixation remain unacceptably high. We developed a computer model of the acromioclavicular joint to better understand the biomechanical contributions of the ligaments that are typically injured. Six fresh frozen human cadaveric shoulders were tested on an AMTI VIVO 6–degree of freedom test platform to measure force-displacement in inferior translation, anteroposterior translation, and internal rotation before and after sequentially transecting the coracoclavicular and acromioclavicular ligaments. These data were used to construct computer models of each specimen. Three-dimensional computed tomographic scans were used to generate a rigid-body dynamics model using the AnyBody Modeling System. The scapula and clavicle were connected by the acromioclavicular joint capsule, the conoid ligament, and the trapezoid ligament. Subject-specific ligament properties were calculated by matching computer predictions to experimental force-displacement data. The calculated free lengths of the conoid, trapezoid, and acromioclavicular ligaments were 13.5 (±3.2), 11.8 (±2.4), and 11.0 (±2.7) mm, respectively. The calculated stiffnesses of the conoid, trapezoid, and acromioclavicular ligaments were 34.3 (±6.3), 28.4 (±3.2), and 33.8 (±8.2) N/mm, respectively. Root mean square deviation (RMSD) of predicted force-displacement curves relative to experimental force-displacement curves (during inferior and anteroposterior translation) was less than 1 mm. For validation of subject-specific models, after ligament properties were calculated, the RMSD of the predicted torque over 15° of internal rotation was 12% of maximum rotational torque (average for 6 specimens). Acromioclavicular disruption results in multidirectional instability, which requires careful consideration of the individual contributions of the injured ligaments. In addition, variations in patient anatomy can significantly affect the biomechanical stability of the reconstruction. Subject-specific models can enhance our understanding of the individual and collective biomechanical contributions of the injured soft tissues to the multiaxial stability of the acromioclavicular joint. These models may also be useful for analyzing and assessing biomechanical stability after various types of surgical reconstruction.